2022
DOI: 10.1177/20503121221094688
|View full text |Cite
|
Sign up to set email alerts
|

Trends in inequality in the coverage of vitamin A supplementation among children 6–59 months of age over two decades in Ethiopia: Evidence from demographic and health surveys

Abstract: Objectives: There is a dearth of evidence on inequalities in vitamin A supplementation in Ethiopia. The goal of this study was to assess the magnitude and overtime changes of inequalities in vitamin A supplementation among children aged 6–59 months in Ethiopia. Methods: We extracted data from four waves of the Ethiopia Demographic and Health Surveys (2000, 2005, 2011, and 2016). The analysis was carried out using the 2019 updated World Health Organization’s Health Equity Assessment Toolkit software that facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
(94 reference statements)
5
3
3
Order By: Relevance
“…Children from the Afar, Somali, SNNPR, and Addis Ababa regions were less likely to receive VAS than children from Tigray regions. This finding is supported by similar studies done in Ethiopia [24], especially in the regions of Afar and Somalia [30]. The possible explanation in the pastoralist regions (Afar and Somali) and SNNPR might be a shortage of healthcare providers and inequality in maternal healthcare service [31].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Children from the Afar, Somali, SNNPR, and Addis Ababa regions were less likely to receive VAS than children from Tigray regions. This finding is supported by similar studies done in Ethiopia [24], especially in the regions of Afar and Somalia [30]. The possible explanation in the pastoralist regions (Afar and Somali) and SNNPR might be a shortage of healthcare providers and inequality in maternal healthcare service [31].…”
Section: Discussionsupporting
confidence: 72%
“…The possible explanation might be better household wealth standing may improve uptake of the supplement through advancing access to health information and mitigating economic barriers for seeking health care. Different studies report Socioeconomic inequality is a major determinant for maternal health service utilization [30][31][32], which indicates maternal health service utilization is low in the poor. One study showed children from the poorest family are more vitamin A deficient compared to those in richer family [33].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently across the survey periods, our study revealed that children in higher wealth quintiles reported higher proportion of Vitamin A supplementation. Similar findings have been reported in Ethiopia [ 14 ] and India [ 15 ]. A plausible explanation for this finding could be that parents in higher wealth quintile households are more likely to have easy access to healthcare facilities [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…Vitamin A supplementation was consistently high among children born to mothers with secondary or higher education across the various survey points. This finding mirrors results from previous studies that have found high Vitamin A supplementation among children whose mothers have secondary or higher education [ 14 , 15 ]. The result from this study may be explained from the perspective that formal education and higher education mothers’ awareness of health and nutritional requirements contribute positively toward Vitamin A supplementation [ 5 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation